Exploring faculty adaptation to course content creation post-COVID-19: perceptions, challenges, and best practices for higher education - Shappee, Lisa (My University, 2026)
This dissertation studied the strategies university faculty utilized in course content delivery following the COVID-19 pandemic, with a focus on perceptions and best practices within a large midwestern public research university. The sudden onset of the pandemic in early 2020 required a transition to Emergency Remote Teaching (ERT), requiring faculty to adopt online teaching platforms and methodologies under significant time constraints. This study sought to understand how these adaptations shaped faculty teaching practices, their utilization of educational technologies, and their broader impact on higher education pedagogy. By analyzing faculty responses to this unprecedented shift, the research highlights lessons learned and the potential for long-term innovations in teaching and faculty development. The study utilized a qualitative case study approach, drawing on three theoretical frameworks, Self-Determination Theory (SDT), the Technology Acceptance Model (TAM), and self-efficacy theory. These frameworks helped to examine faculty motivations, technological adoption, and pedagogical effectiveness. Data collection involved semi-structured interviews with faculty and syllabi analysis. These methods provide both a detailed account of the instructional changes implemented and insight into the faculty experience of navigating these changes. This study offers recommendations that extend beyond short-term faculty training to emphasize the institutional conditions that sustain effective online and hybrid teaching. Findings highlight the importance of structured course design, intentional technology integration, clear communication, balanced workload expectations, and ongoing instructional support. The study also contributes to theoretical understanding by demonstrating how faculty motivation, autonomy, and self-efficacy evolved alongside technology adoption. Overall, the findings suggest that post-pandemic instructional change reflects sustained professional growth supported by institutional environments rather than ERT.
Keywords: Emergency remote teaching; Faculty adapatation; Instructional change; Online teaching; Self-Determination Theory; Teaching self-efficacy